Redox-mediated kick-start of mitochondrial energy metabolism drives resource-efficient seed germination - Nietzel, Thomas; Poschet, Gernot; Büttner, Michael; Wirtz, Markus; Hell, Rüdiger (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Seeds preserve a far developed plant embryo in a quiescent state. Seed metabolism relies on stored resources and is reactivated to drive germination when the external conditions are favorable. Since the switchover from quiescence to reactivation provides a remarkable case of a cell physiological transition we investigated the earliest events in energy and redox metabolism of Arabidopsis seeds at imbibition. By developing fluorescent protein biosensing in intact seeds, we observed ATP accumulation and oxygen uptake within minutes, indicating rapid activation of mitochondrial respiration, which coincided with a sharp transition from an oxidizing to a more reducing thiol redox environment in the mitochondrial matrix. To identify individual operational protein thiol switches, we captured the fast release of metabolic quiescence in organello and devised quantitative iodoacetyl tandem mass tag (iodoTMT)-based thiol redox proteomics. The redox state across all Cys peptides was shifted toward reduction from 27.1% down to 13.0% oxidized thiol. A large number of Cys peptides (412) were redox switched, representing central pathways of mitochondrial energy metabolism, including the respiratory chain and each enzymatic step of the tricarboxylic acid (TCA) cycle. Active site Cys peptides of glutathione reductase 2, NADPH-thioredoxin reductase a/b, and thioredoxin-o1 showed the strongest responses. Germination of seeds lacking those redox proteins was associated with markedly enhanced respiration and deregulated TCA cycle dynamics suggesting decreased resource efficiency of energy metabolism. Germination in aged seeds was strongly impaired. We identify a global operation of thiol redox switches that is required for optimal usage of energy stores by the mitochondria to drive efficient germination.
Gesehen am 06.02.2020